Pengaruh Pengendalian Internal dan Kesesuaian Kompensasi Terhadap Kecenderungan Kecurangan Akuntansi pada PT. Telkom Witel Sul-Sel Makassar - Muzdalifah; Sahidah (Insan Cita Bongaya Research Journal, 2023)
This study aims to determine the effect of internal control over accounting fraud inclination, influences the suitability of compensation to the tendency of accounting fraud and influences internal control and compliance compensation against the tendency of the accounting fraud. The population in this study is the manager and employees of PT. Telkom Witel Sul-Sel Makassar as many as 70 people with samples from the questioner back to the analysis tool used is multiple linear regression. The results of this study Show that (1) internal control is not a negative effect on the tendency off accounting fraud, (2) the suitability of the compensation is not a negative effect on the tendency off accounting fraud.